2007
DOI: 10.1143/jjap.46.7875
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Etch Rate Behavior of 4H–SiC Using Chlorine Trifluoride Gas

Abstract: The etch rate of single-crystalline 4H–SiC is studied using chlorine trifluoride gas at 673–973 K and atmospheric pressure in a cold wall horizontal reactor. The 4H–SiC etch rate can be higher than 10 µm/min at substrate temperatures higher than 723 K. The etch rate increases with the chlorine trifluoride gas flow rate. The etch rate is calculated by taking into account the transport phenomena in the reactor including the chemical reaction at the substrate surface. The flat etch rate at the higher substrate te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…The silicon carbide etching could continue even after the carbon film was formed. 3,6 Thus, the carbon film obtained in this study was not dense; the chlorine trifluoride gas could be transported through the carbon film to the silicon carbide surface to continuously cause the etching.…”
Section: P442mentioning
confidence: 86%
“…The silicon carbide etching could continue even after the carbon film was formed. 3,6 Thus, the carbon film obtained in this study was not dense; the chlorine trifluoride gas could be transported through the carbon film to the silicon carbide surface to continuously cause the etching.…”
Section: P442mentioning
confidence: 86%
“…For this purpose, the authors have developed a chemical etching method of SiC using chlorine trifluoride gas (2)(3)(4)(5)(6)(7). Our previous Study (7) showed that the etch pits formed at low temperatures might have a relationship with dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The material of the horizontal cold-wall reactor used in these studies was fused silica. When the highly reactive gases are supplied into the chamber, the inner side wall of the fused silica chamber is exposed and etched by the gases.…”
Section: Introductionmentioning
confidence: 99%